2012
DOI: 10.1590/s1413-70542012000300010
|View full text |Cite
|
Sign up to set email alerts
|

Development and antioxidant capacity of sapota pulp Jelly (Quararibea cordata Vischer)

Abstract: Sapote (Quararibea cordata Vischer), also known as a chupa-chupa, is originated from the Brazilian, Peruvian and Colombian Amazon. The pulp of the ripe fruit is edible, fibrous, of intense orange color, sweet flavor and aromatic. Since the fruit is known in the Amazon only in its domesticated state, this work becomes necessary. With the aim of meeting the demand for new products in domestic and international markets, sapota pulp jelly has been developed. The jelly was assessed for moisture, ash, lipids, protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
1
3
0
1
Order By: Relevance
“…These results were similar to those previously reported by Kim and Padilla-Zakour [39], who reported values of 132.9 mg GAE 100 g −1 for cherry jelly and 144.3 mg GAE 100 g −1 for plum jam. In addition, the current findings agreed with a recent study [40], which observed that the processing of sapota pulp jelly showed an increase of 4.8 times from the fresh fruit to the processed fruit. Heat treatment can modify the content of phenolic compounds due to disruption of the plant cell wall, with the consequent release of these compounds [41].…”
Section: Addition Of 1% Citric Acidsupporting
confidence: 93%
“…These results were similar to those previously reported by Kim and Padilla-Zakour [39], who reported values of 132.9 mg GAE 100 g −1 for cherry jelly and 144.3 mg GAE 100 g −1 for plum jam. In addition, the current findings agreed with a recent study [40], which observed that the processing of sapota pulp jelly showed an increase of 4.8 times from the fresh fruit to the processed fruit. Heat treatment can modify the content of phenolic compounds due to disruption of the plant cell wall, with the consequent release of these compounds [41].…”
Section: Addition Of 1% Citric Acidsupporting
confidence: 93%
“…The total antioxidant activity varied significantly from 13.45% to 15.39% in the extract, with a concentration of 0.2 mg.mL −1 . In study by Carvalho, Damiani, Asquieri, Orsi, and Nishi (2012), the antioxidant potential was also determined by the scavenging ability in relation to DPPH. In the former study, the total antioxidant activity was 27.85% (10.65% in the alcoholic extract and 16.27% in the aqueous extract).…”
Section: Discussionmentioning
confidence: 99%
“…The degradation the products could be isomers of carotenoids or molecular fragments (Singh et al, 2008). Analysis of the total carotenoid content of the pulp of sapota jelly showed a loss of 97.5% when compared with the fresh fruit, which was the highest loss found in a low-calorie mixed Brazilian cerrado fruit jam; despite these losses, sapota jelly could still suffice for the daily intake of vitamin A (Carvalho et al, 2012).…”
Section: Resultsmentioning
confidence: 94%